Perspective model of electronic tax document flow - Lixia, Xiao (Journal of the Belarusian State University. Economics, 2018)
The article presents the author’s model of introducing tax documents. The results and step-by-step process of the electronic tax accounting system are described. The detailed scheme of a control system of electronic tax document flow is submitted. States the specificity and peculiarities of implementation of electronic document management system, consider steps to ensure the functionality of electronic tax records.
Keywords: tax system; taxation process; tax document management; tax accounting; tax structures